Pengaruh Tambahan Ekoenzim dengan Level Berbeda pada Indeks Kuning Telur, Nilai HU, dan Bobot Tetas pada Ayam IPB-D1 - Juliana Monika Nepa (JURNAL RISET RUMPUN ILMU HEWANI, 2025)
The objective of this study was to analyze the additional effect of eco-enzymes mixed in drinking water on the haught unit value, egg yolk index, and hatch weight of IPB-D1 chickens. A total of 96 chickens were used, comprising 72 females and 24 males. This study used a completely randomized design (CRD) with 4 treatments and 6 replicates. The treatments administered were: P1 = drinking water without eco-enzymes (control), P2 = 1 cc eco-enzymes/L drinking water/3 days, P3 = 2 cc eco-enzymes/L drinking water/3 days, P4 = 3 cc eco-enzymes/L drinking water/3 days. A total of 72 eggs were used to observe egg interior quality, with 3 eggs used per treatment per replicate. A total of 216 eggs were used for hatch weight (9 eggs per treatment and per replicate). The variables measured were egg yolk index, HU value, and hatch weight. Statistical analysis results demonstrated that there were significant differences (P<0.05) in hatched weight, HU value, and egg yolk index. Conclusion: Adding eco-enzymes to drinking water at a dose level of 2 mL/L of drinking water every 3 days can increase the egg yolk index, HU value, and hatch weight of IPB-D1 chickens. Further research is needed on eco-enzymes in chickens and different levels of eco-enzyme dosage.